2011
DOI: 10.2337/db10-0452
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation Increases ChREBP Protein Content and Transcriptional Activity in the Liver

Abstract: OBJECTIVECarbohydrate-responsive element–binding protein (ChREBP) is a key transcription factor that mediates the effects of glucose on glycolytic and lipogenic genes in the liver. We have previously reported that liver-specific inhibition of ChREBP prevents hepatic steatosis in ob/ob mice by specifically decreasing lipogenic rates in vivo. To better understand the regulation of ChREBP activity in the liver, we investigated the implication of O-linked β-N-acetylglucosamine (O-GlcNAc or O-GlcNAcylation), an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
197
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(216 citation statements)
references
References 38 publications
8
197
0
8
Order By: Relevance
“…Previous reports have shown that the loss of OGA in mice leads to defects in metabolic homeostasis, culminating in obesity and insulin resistance [26], and that the overexpression of OGA in db/db mice significantly improves the lipid profile in liver [45]. Consistently, we found impaired insulin signalling and glucose uptake capacity in myotubes after OGA knockdown or treatment with PUGNAc or D-GlcNAc, with concurrent increased O-GlcNAcylation and mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 87%
“…Previous reports have shown that the loss of OGA in mice leads to defects in metabolic homeostasis, culminating in obesity and insulin resistance [26], and that the overexpression of OGA in db/db mice significantly improves the lipid profile in liver [45]. Consistently, we found impaired insulin signalling and glucose uptake capacity in myotubes after OGA knockdown or treatment with PUGNAc or D-GlcNAc, with concurrent increased O-GlcNAcylation and mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, carbohydrate-responsive element-binding protein (ChREBP) contributes to metabolic reprogramming in tumors through inhibition of mitochondrial respiration and up-regulation of aerobic glycolysis, de novo lipogenesis, and nucleotide biosynthesis (39). ChREBP O-GlcNAcylation stabilizes the protein, leading to increased transcription of ChREBP glycolytic and lipogenic target genes L-type pyruvate kinase, acetyl-CoA carboxylase, and fatty acid synthase (40,41). O-GlcNAcylation of the transcription factor Sp1 activates a cholesterolgenic program through transcriptionally increasing the expression of the SREBP1 (sterol response element-binding protein 1) and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (42).…”
mentioning
confidence: 99%
“…Des études récentes ont également permis de montrer que l'activité de ChREBP pouvait être modulée par des modifications post-traductionnelles comme la O-GlcNAcylation ou l'acétylation [15][16][17]. En réponse au glucose, la protéine ChREBP est acétylée sur la lysine 672 (résidu localisé dans le domaine de liaison à l'ADN) Figure 1A) [23].…”
Section: Régulation De Chrebp Par Acétylation Et O-glcnacylationunclassified
“…Par la suite, notre laboratoire a montré une interaction directe entre ChREBP et l'OGT dans des hépatocytes en culture primaire et dans le foie in vivo. La O-GlcNAcylation qui en résulte conduit à la stabilisation de ChREBP et à l'augmentation de son activité transcriptionnelle sur ses gènes cibles [16]. Outre ChREBP, des régulateurs clefs du métabolisme énergétique, Un rôle controversé pour ChREBP dans la sensibilité à l'insuline hépatique L'importance du facteur de transcription ChREBP dans le contrôle de l'homéostasie énergétique a été mise en évidence par la caractérisa-tion phénotypique de plusieurs modèles animaux [5,[25][26][27].…”
Section: Chrebp Et Sensibilité à L'insuline : Une Relation Complexe ?unclassified